"Teaching old dogs new tricks" - POCUS Education for Senior Faculty - Daniel Restrepo; Thomas Heyne; Christine Schutzer; Renee Dversdal (CINQUILL Medical Publishers Inc., 2023)
Point of care Ultrasound (POCUS) is a growing diagnostic modality across a variety of specialties and is increasingly being taught in undergraduate medical education. Uptake within internal medicine has been slow but is becoming more commonplace. Training of extant hospital medicine faculty, including senior members, in POCUS is an unmet need in graduate medical education with significant pedagogical and patient safety implications. With this in mind, we created a training program for the core teaching faculty at our academic internal medicine residency program. The experiential, hands-on curriculum explored the reasoning behind concepts and emphasized psychological safety for senior faculty learners and was successful and well-received. In our piece, we aim to explore the existing literature around training this unique population in POCUS and report on our single-center experience. We also provide a framework for how our program succeeded, collate tips derived from the expert ultrasound teachers and list pearls learned while teaching these experienced educators. Although this worthwhile effort requires planning and support, it was appreciated even by senior faculty.